Gravity anomalies over extinct spreading centres: A new evidence of an aborted ridge in the South Atlantic Ocean - Constantino, Renata Regina [UNESP]; Hackspacher, Peter Christian [UNESP]; Costa, Iago Sousa Lima; Molina, Eder Cassola; De Souza, Iata Anderson [UNESP] (Oxford University Press (OUP), 2019)
An aborted ridge has been suggested in the Vema region, South Atlantic Ocean, and we investigate it in terms of residual gravity anomalies and half spreading rate. Gravity signature over extinct spreading centres displays residual gravity anomaly lows flanked by positive highs with systematic palaeo-spreading rate dependency. The amplitude and half-widths of the gravity lows are smaller for fast spreading rates, a relationship that has been presented for several well-constrained extinct spreading centres, such as Coral Sea and Labrador Sea, both regarded in this work for comparative purposes. The residual gravity anomalies are estimated from the removal of a long-wavelength regional trend and the gravitational effect of basement and suprabasement sources. The global sediment thickness model of NOAA is used to evaluate the sediment layer and a compaction model that fits observed density values is also considered. The basement topography is obtained from gravity field inversion and shows clearly the extinct spreading axes of the Coral Sea Basin and Labrador Sea, which are not evident from the bathymetric data set due to sedimentary deposits that lie over them. The Vema basement shows an NS structure previously suggested as the Vema Aborted Ridge (VAR), which does not coincide with the morphological feature known as the Vema Channel. Over the VAR, we have found amplitudes and half-widths in function of their half spreading rate typical from well-constrained extinct spreading centres, indicating that the structure might actually be an aborted ridge.
Keywords: Atlantic Ocean; Gravity anomalies and Earth structure; Satellite gravity; Submarine tectonics and volcanism